2020
DOI: 10.1177/0954406220959376
|View full text |Cite
|
Sign up to set email alerts
|

Adhesively bonded joints in components manufactured via selective laser melting

Abstract: Additive manufacturing has gained increasing attention in recent years in numerous industrial sectors due to its inherent characteristics, e.g. tool-free production and unprecedented freedom of design. However, in some applications such as heat exchangers the design has to follow certain restrictions, e.g. to allow for the removal of unfused powder, which can be enclosed in cavities. Moreover, in case multi-material parts are considered, the use of different powders during processing is often uneconomical sinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…With the progressive application of additive manufacturing processes, the joining of additively manufactured components is also becoming more and more relevant [34]. The results obtained in this study indicate that the inherent surface roughness of additively manufactured parts has a beneficial effect on the bond strength of metal-CFRP hybrid joints in comparison to flat, unstructured surfaces.…”
Section: Discussionmentioning
confidence: 75%
“…With the progressive application of additive manufacturing processes, the joining of additively manufactured components is also becoming more and more relevant [34]. The results obtained in this study indicate that the inherent surface roughness of additively manufactured parts has a beneficial effect on the bond strength of metal-CFRP hybrid joints in comparison to flat, unstructured surfaces.…”
Section: Discussionmentioning
confidence: 75%
“…Maamoun et al 16 formed AlSi10Mg alloy under different SLM process parameters and investigated the effects of laser process parameters on relative density, porosity, surface roughness, and dimensional accuracy, and they developed the optimized range of SLM process parameters for each characteristic to ensure the quality of printed samples. Koch et al 17 used different laser process parameters to fabricate AlSi10Mg samples via SLM. They analyzed the effects of laser power and building direction on surface topography and found that surface properties significantly influence the adhesion properties between samples and substrates.…”
Section: Introductionmentioning
confidence: 99%
“…In all of these sectors, abrasive behaviour is non-desirable and can result in damage with serious consequences. Therefore, many studies [11][12][13] have focused on improving the surface quality of additive manufactured parts, since additive manufactured structures without any subsequent treatment are not to be considered ideal friction partners, due to their porous surface. In most studies, the high surface roughness is decreased by subtractive methods as turning and polishing [14][15][16] in order to enhance the mechanical and tribological behaviour.…”
Section: Introductionmentioning
confidence: 99%